„Rozwiecznione w horyzont”. Wieki średnie Stanisława Barańczaka - Bogalecki, Piotr (Przestrzenie Teorii, 2016)
The article provides an interpretation of Middle Ages, a poem from Stanisław Barańczak’s debut publication Facial Corrections (1968). Focussing on the way that numerous examples of zeugma and syllepsis are used, the author argues that this poem, which was probably inspired by the first Polish publication of the Waning of the Middle Ages by J. Huizinga, was created through the poet’s reflections on the structure of messianic time (kairos). As such it can be seen as both a polemic with materialism and a criticism of Christianity. In this way Middle Ages proves to be the first of post-secular Barańczak’s poems which herald the wealth of spiritual explorations in his later works.